Design Retaining Wall Pada Sungai Weybolar Kabupaten Maluku Tenggara Barat - Kdise, Saul Fredrik Enricko; Suhudi, Suhudi; sulistyani, kiki frida (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Land is an important aspect in the planning of construction. Because the land has the standing of a building. Therefore, it is important to take into account the stability of the soil. One of the ways used to control the stability of the ground so as nor to experience sliding is to build a retaining wall. Planning retaining wall is located on the Weybolar River, West Southeast Maluku District and located on seismic zone 5. On this plan, the data used comes from the Public Works Department of Mining and Energy, West Southeast Maluku District. The planned retaining wall is a kind of gravity. So this building can function properly, then the stability of the building should also be good. Therefore, the author tries to analyze the stability of the retaining wall against the danger of rolling and sliding with normal water level condition without the earthquake, with the earthquake and flood water level condition without the earthquake, and with earthquake. Analyze using the Rankine formula. The result is SFsliding 1,77 > 1,5 and 1,38 > 1,2, SFbolters 2,5 > 1,5 and 1,2 â¥ 1,2 (for normal condition without and with the earthquake) and SFsliding 1,93 > 1,5 and 1,38 > 1,2, SFbolters 2,97 > 1,5 and 1,56 > 1,2 (for flood condition without and with the earthquake), it turns out safely. This writing is also included in the calculation of the total budget plan is Rp. 191.798.000 Keyword: Weybolar River, Retaining wall, Stability.